Altered expression of glycan genes in cancers induced by epigenetic silencing and tumor hypoxia: Clues in the ongoing search for new tumor markers - Reiji Kannagi; Keiichiro Sakuma; Keiko Miyazaki; Khe‐Ti Lim; Akiko Yusa; Jun‐Jie Yin; Mineko Izawa (2009)
( Cancer Sci 2010; 101: 586–593) The glycan molecules that preferentially appear in cancers are clinically utilized as serum tumor markers. The exact reason, however, why glycans are useful as tumor markers remain elusive. Here, we will summarize lessons learned from well‐established cancer‐associated glycans, and propose strategies to develop new cancer markers. Our recent results on cancer‐associated glycans, sialyl Lewis A and sialyl Lewis X, indicated that the repressed transcription of some glycan genes by epigenetic silencing during early carcinogenesis, and the transcriptional induction of some other glycan genes by tumor hypoxia accompanying cancer progression at locally advanced stages, are two major factors determining cancer‐associated glycan expression. Multiple genes are involved in glycan synthesis, and epigenetic silencing of a part of such genes leads to accumulation of glycans having truncated incomplete structures, which are readily detected by specific antibodies. Glycans are very unique and advantageous as marker molecules because they are capable of reflecting epigenetic silencing in their structures. Transcriptional induction of some glycan genes by tumor hypoxia at the later stages produces further glycan modifications, such as an unusual increase of the N ‐glycolyl sialic acid residues in the glycan molecules. The entire process of malignant transformation thus creates abnormal glycans, whose structures reveal the effects of both epigenetic silencing and tumor hypoxia. The second advantage of a glycan marker over a proteinous marker is that they can reflect the plurality of genetic anomalies in a singular molecule, as it is synthesized by the cooperative action of multiple genes. Glycans are sometimes covalently bound to well‐known cancer‐associated proteins, such as CD44v, and this eventually contributes to a high cancer specificity and functional relevancy in cancer progression.